مستوى الطموح وعلاقته بالتعلم الذاتي (دراسة ميدانية على عينة من تلاميذ السنة الثالثة ثانوي بمدينة ورقلة) (مجلة الواحات للبحوث والدراسات, 2020)
The Present Study Aims At Uncovering The Relationship Between The Level Of Ambition And Self-Learning And The Extent Of The Contribution Of The Specialization Factor In Creating Differences In This Relationship. We Relied On A Sample Of 300 Students And Two Measurement Tools, Guglimeno). , And The Descriptive Descriptive Approach Was Adopted, And Statistical Processing Was Done Using The Statistical Program (Spss). The Results Were As Follows:1-There Is A Statistically Significant Relation Between The Level Of Ambition And Its Relation To Self-Learning Among Secondary School Students2-There Are Statistically Significant Differences In The Level Of Ambition Level Among Secondary School Students Due To The Specialization Variable.3-There Are Statistically Significant Differences In Level And Self - Learning Among Secondary School Students Due To Specialization Variable    Keywords -Level Of Ambition, Self-Learning, Third Secondary Students.